Presidential address - Research and development of spices in India - EDISON, S (Journal of Spices and Aromatic Crops, 1998)
From time immemorial spices and India have always been synonymous and been part of history ever since the days of landing of Vasco da Gama near Cali cut in 1498. Spices are grown in about 2.1 million ha in India producing about 2.5 million tonnes annually. We had the prestige of exporting nearly 40% of the world’s requirement of spices at one time but it slid down to about 15-18% in recent years in physical terms, although the value has increased.